2008
DOI: 10.1177/0013161x07306454
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation and the New Leader Agenda: Outcomes and Lessons from Michigan

Abstract: Purpose: This research examined whether the removal of certification and other requirements led to larger or more diverse applicant pools for superintendent positions in Michigan. Michigan has not had any degree or certification requirements for educational administrators for many years and provided an empirical test of whether deregulation draws new talent into the field. Research Design, Methods: The research was designed as a state-level case study employing quantitative and qualitative methods to develop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…By 2008, 43 states required the ISLLC standards or a modified version in their administrative licensure standards and leadership preparation curricula (CCSSO, 2008). Initially developed in 1996, the ISLLC standards were revised in 2008(NPBEA, 2015 and are now called the Professional Standards for Educational Leaders. The standards have been referenced when defining building-and district-level leadership functions by the Educational Leadership Constituent Council (ELCC) of the National Council for Accreditation of Teacher Education (NCATE; NPBEA, 2011a, 2011b), used by leadership preparation providers to attain state and national accreditation of their principal and superintendent programs.…”
Section: Influence Of Isllc Standardsmentioning
confidence: 99%
See 1 more Smart Citation
“…By 2008, 43 states required the ISLLC standards or a modified version in their administrative licensure standards and leadership preparation curricula (CCSSO, 2008). Initially developed in 1996, the ISLLC standards were revised in 2008(NPBEA, 2015 and are now called the Professional Standards for Educational Leaders. The standards have been referenced when defining building-and district-level leadership functions by the Educational Leadership Constituent Council (ELCC) of the National Council for Accreditation of Teacher Education (NCATE; NPBEA, 2011a, 2011b), used by leadership preparation providers to attain state and national accreditation of their principal and superintendent programs.…”
Section: Influence Of Isllc Standardsmentioning
confidence: 99%
“…Some states provide avenues for non-educators to obtain administrative licensure, either by permitting them to enroll in alternative programs (such as the Broad Superintendents Academy) or by not requiring any administrative training. Smith (2008) reported that most candidates in alternative programs are educators. Recent data on the superintendency found that 95% of the nation's practicing school superintendents in 2010 reported holding a valid superintendent license, while 86% of urban superintendents (student enrollments of 25,000 or more) possessed this credential (Kowalski, McCord, Petersen, Young, & Ellerson, 2011).…”
Section: Alternative Administrative Licensure Optionsmentioning
confidence: 99%
“…More recently, Leadership for Educational Equity has started preparing Teach for America alumni for leadership roles (Sawchuk, 2014). The few studies that have analyzed school districts' hiring practices suggest that school boards still want to hire leaders with graduate degrees (Smith, 2008), but they are more concerned about candidates' skill sets than how administrative credentials were acquired (Brown et al, 2011).…”
Section: Rigorously Evaluating Traditional and Alternative Leadershipmentioning
confidence: 99%
“…Little is known about the early stages of career pathways into educational administration (Davis, Gooden, & Bowers, 2017), and what is known is almost exclusive to campus-level leaders. Among the studies that investigate the career experiences of district-level leaders (e.g., Petersen, Fusarelli, & Kowalski, 2008; Roberts, Hanna, & Womack, 2012; Smith, 2008), most focus on the novice superintendent, investigating their experiences after obtaining the position. Much like the research on building-level leadership career pathways (Davis et al, 2017), those that focus on latter portions of superintendent careers, tend to focus on turnover and its causes (e.g., Alsbury, 2003, 2008; Grissom & Andersen, 2012; Grissom & Mitani, 2016; Natkin, Cooper, Alborano, Padilla, & Ghosh, 2003).…”
mentioning
confidence: 99%
“…This is a critical issue as preparation programs and employing districts share responsibility in the training of district chief executives. Indeed, for states in which no certification has been required (Smith, 2008), questions about training, experience, and turnover are heightened even more. Nevertheless, as noted by Orr (2006):The 2-year learning curve that some superintendents described experiencing suggests that existing preparatory experiences generally are insufficient.…”
mentioning
confidence: 99%